Living Amid Infrastructure Inequality: A Social Portrait of The Scavenger Community in Savana Settlement, Makassar City - Ahmad, M. Ridwan Said; Dg Ngai, Mauliyanda Sam; Ramadhani, Kia; Fadzilah, Najmi Nurul (Citra Media Publishing, 2025)
Infrastructure inequality in Indonesia’s urban areas remains a structural issue that directly affects the urban poor. While city development continues to emphasize modernization and spatial aesthetics, marginalized groups, such as waste-picker communities, are excluded from accessing basic services and the right to adequate living space. This study aims to understand how urban poor communities adapt and build social resilience in the face of structural exclusion. By examining the everyday life dynamics of the waste-picker community in Savana Settlement, Makassar City, who live under conditions of severe infrastructural deprivation, this research employs a descriptive qualitative approach. Data were collected through in-depth interviews, field observations, and documentation to uncover the forms of social organization, survival strategies, and the meanings of space within the community. The findings reveal that the waste-picker community develops adaptive strategies grounded in social solidarity, informal economic networks, and collective labor. The absence of adequate infrastructure paradoxically reinforces collective awareness and a sense of belonging, shaping a distinctive form of social resilience built upon shared experiences. Furthermore, the Savana space functions not only as a physical setting but also as a symbolic domain that shapes their social identity, distinguishing them from residents of formal urban areas.